Development of organophosphate hydrolase activity in a bacterial homolog of human cholinesterase - Legler, Patricia M.; Boisvert, Susanne M.; Compton, Jaimee R.; Millard, Charles B. (Frontiers in Chemistry, 2014)
We applied a combination of rational design and directed evolution (DE) to Bacillus subtilis p-nitrobenzyl esterase (pNBE) with the goal of enhancing organophosphorus acid anhydride hydrolase (OPAAH) activity. DE started with a designed variant, pNBE A107H, carrying a histidine homologous with human butyrylcholinesterase G117H to find complementary mutations that further enhance its OPAAH activity. Five sites were selected (G105, G106, A107, A190, and A400) within a 6.7 Å radius of the nucleophilic serine O. All 95 variants were screened for esterase activity with a set of five substrates: pNP-acetate, pNP-butyrate, acetylthiocholine, butyrylthiocholine, or benzoylthiocholine. A microscale assay for OPAAH activity was developed for screening DE libraries. Reductions in esterase activity were generally concomitant with enhancements in OPAAH activity. One variant, A107K, showed an unexpected 7-fold increase in its kcat/Km for benzoylthiocholine, demonstrating that it is also possible to enhance the cholinesterase activity of pNBE. Moreover, DE resulted in at least three variants with modestly enhanced OPAAH activity compared to wild type pNBE. A107H/A190C showed a 50-fold increase in paraoxonase activity and underwent a slow time- and temperature-dependent change affecting the hydrolysis of OPAA and ester substrates. Structural analysis suggests that pNBE may represent a precursor leading to human cholinesterase and carboxylesterase 1 through extension of two vestigial specificity loops; a preliminary attempt to transfer the Ω-loop of BChE into pNBE is described. pNBE was tested as a surrogate scaffold for mammalian esterases. Unlike butyrylcholinesterase and pNBE, introducing a G143H mutation (equivalent to G117H) did not confer detectable OP hydrolase activity on human carboxylesterase 1. We discuss the importance of the oxyanion-hole residues for enhancing the OPAAH activity of selected serine hydrolases.